Effect of Different Types of Carrier and Stripping Agent in Liquid Membrane Formulation for Silver Extraction by using Kerosene and Corn Oil - kaswadi, amir; Mohd Aripen, Nur Shahirah; Muhammad Naim Najmie bin Sokarno,; MOHD KHUSHAIRI, MUHAMMAD ALFIQ HAIKAL (Multidisciplinary Applied Research and Innovation, 2022)
As the world undergoes rapid urbanization, the usage of natural sources growth has increased rapidly to a greater amount causing the rate of waste generation to increase align with it. As the waste production greatly increase, the rate of pollution has also increase especially water pollution. The water pollution is caused by the heavy metals contains in the water. In order to treat the contaminated water, Liquid Membrane has been introduced as one of the technologies that can extract the heavy metals from the water. Several characteristics were studied, including different types of carrier, and stripping agent. This technical paper is written to show the extraction of silver using Kerosene as a diluent and Triotylamine (TOA) and Tridodecylamine(TDA) as a carrier and Sodium Hydroxide (NaOH) as a stripping agent.Keywords: Silver Extraction, Liquid Membrane, Water, Carrier, Stripping Agent